![23x - 16 = 14 - 17x 23x - 16 = 14 - 17x](https://tex.z-dn.net/?f=23x+-+16+%3D+14+-+17x)
Soluções para a tarefa
Respondido por
1
Resposta:
S = { 0,75 }
Explicação passo-a-passo:
.
. 23x - 16 = 14 - 17x
. 23x + 17x = 14 + 16
. 40x = 30
. x = 30 ÷ 40
. x = 0,75
.
(Espero tyer colaborado)
gigi419423:
obrigado
Respondido por
0
Explicação passo-a-passo:
Equação do primeiro grau:
23x — 16 = 14 — 17x
23x + 17x = 14 + 16
40x = 30
x = 30/40
x = 3/4
Espero ter ajudado bastante!)
Perguntas interessantes
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Geografia,
10 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás